HUBUNGAN KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN SALON KECANTIKAN DI KECAMATAN PADANG BARAT - Hayati, Hasanatul; Katin, Yusmar Emmy; Rahmiati, Rahmiati (Journal of Home Economics and Tourism, 2012)
The purposes of this study are (1) to determine the quality of service provided to the customer of beauty salon in sub-district of West Padang. (2) to determine the level of satisfaction of customer who visit the beauty salon in sub-district of West Padang. (3) to determine the relationship of service quality to the customer satisfaction in the beauty salon. The research is descriptive quantitaive research using correlation, where the samples are taken from 37 customers who visited the beauty salon. In the sampling, the researcher using method of incidental sampling which used questionnaire that had been tested validity and reliability, and questionnaires were analyzed with descriptive statistic, test requirements analysis, correlation analysis and hypothesis testing. The results showed that: (1) The quality of service at beauty salon in sub-district of West Padang in the position of High category. (2) Customer satisfaction at beauty salon in sub-district of West Padang in the position of High category. (3) There is positive relationship between service quality to the customer satisfation in the beauty salon in sub-distict of West Padang.